The Potential of Blind Collaborative Justice Testing the Impact of Expert Blinding and Consensus Building on the Validity of Forensic Testimony - Wong, Carolyn (RAND Corporation, 2015)
Biased expert testimony is a leading cause of wrongful convictions, and new techniques are needed to reduce such biases. RAND researchers conducted an experimental investigation of two potential contributors to biased testimony within adversarial litigation involving forensic evidence: (1) experts' knowledge of their party representation (i.e., prosecution vs. defense counsel), and (2) lack of input from the relevant scientific community.